Minimally Invasive Prostate Convective Water Vapor Energy Ablation: A Multicenter, Randomized, Controlled Study for the Treatment of Lower Urinary Tract Symptoms Secondary to Benign Prostatic Hyperplasia - McVary, Kevin T; Gange, Steven N; Gittelman, Marc C; Goldberg, Kenneth A; Patel, Kalpesh; Shore, Neal D; Levin, Richard M; Rousseau, Michael; Beahrs, J. Randolf; Kaminetsky, Jed; Cowan, Barrett E; Cantrill, Christopher H; et al. (The Journal of urology, 2016)
Purpose This report reveals the results of a multicenter, randomized, controlled study using transurethral prostate convective water vapor thermal energy to treat lower urinary tract symptoms associated with benign prostatic hyperplasia. Materials and Methods Men 50 years old or older with an International Prostate Symptom Score of 13 or greater, maximum flow rate of 15 ml per second or less and prostate size 30 to 80 cc were randomized 2:1 between thermal therapy with the Rezūm® System and control. Thermal water vapor was injected into the transition zone and median lobe as needed. The control procedure was rigid cystoscopy with simulated active treatment sounds. The primary end point compared International Prostate Symptom Score reduction at 3 months. Treatment subjects were followed for 12 months. Results There were 197 men randomized (active 136, control 61). Thermal therapy and control International Prostate Symptom Score was reduced by 11.2 ± 7.6 and 4.3 ± 6.9 respectively (p <0.0001). Treatment subject baseline International Prostate Symptom Score of 22 decreased at 2 weeks (18.6, p=0.0006) and by 50% or greater at 3, 6 and 12 months, p <0.0001. The peak flow rate increased by 6.2 ml per second at 3 months and was sustained throughout 12 months (p <0.0001). No de novo erectile dysfunction was reported. Adverse events were mild to moderate and resolved quickly. Conclusions Convective water vapor thermal therapy provides rapid and durable improvements in benign prostatic hyperplasia symptoms and preserves erectile and ejaculatory function. Treatment can be delivered in an office or hospital setting using oral pain medication and is applicable to all prostate zones including the median lobe.